THE IMPACT OF CAPITAL FORMATION ON INDUSTRIAL GROWTH IN NIGERIA: LESSONS FROM SOUTH KOREA EXPERIENCE - Ogungbe Ambrose Sola (Graduate School of International Studies Ajou University, 2014)
ABSTRACT The paper emanate from the framework of the national plan of the nation that envision Nigeria to be among the first twenty economies by the year 2020 and it focuses on the impact of capital formation, national savings on industrial growth and the policy lessons that could be learn from South Korea’s industrial policy. In order to widening the nation’s economic opportunities, it stresses the role of national savings as means to kick start the infrastructure development in terms of local financing, based on the prospect of home-grown economic development that could catalyzes the appropriate 3Is (Instrument, Institution and Investment) leading the oil rich nation into being the acclaimed giant of Africa. Most especially, now that it has just been declared the largest economy with a GDP of $509 Billion in Africa overtaking Egypt and South Africa in the region after her just concluded economic rebasing. The theoretical framework upon which this work is based includes the Harrod-Domar model of economic growth and Gerschenkron’s great spurt theory. The former opines that economic growth stems from the rate of savings which has a direct bearing on the physical capital accumulation and hence on capital output ratio. The latter on the other hand incorporates population growth (which is included as a control variable in the model used for this research work) as a basic factor in fostering industrialization. The result of this study shows that National savings and capital formation is paramount to spur industrial growth in Nigeria. Key words: Capital formation, national savings, diversification, industrialization.
학위논문(석사)--아주대학교 Graduate School of International Studies :국제통상학과,2014. 8